Intestinal parasites in children and soil from Turbaco, Bolívar and associated risk factors (2016)
Objective To determine the frequency of intestinal parasites in children and soil from Turbaco- Bolívar and associated risks factors.Methods Analytical study in which 390 children between 2 and 12 years old from 10 neighborhoods of Turbaco were included, whose legal representatives gave informed consent. Three serial samples of feces and 10 soil samples were processed. Risk factors were determined through an interview. Physicochemical and structural characteristics of soils were also evaluated.Results Parasites were found in 30.5 % of children. 162 parasites were observed; the most frequent protozoan was Endolimax nana (30.3 %) and in terms of helminthes, the most frequent was Ascaris lumbricoides (4.9 %). No statistical association between age or sex and intestinal parasites (p0.05) or between risk factors and intestinal parasites (p0.05) was found. Low frequencies of intestinal parasites were encountered in soil samples, being more common Entamoeba spp., Giardia spp., and Ascaris lumbricoides. Neighborhoods of Turbaco had sandy dry soil with low content of ions, low conductivity and low organic matter.Conclusion This study showed a low frequency of intestinal parasites in feces and soils. Despite this, pathogenic parasites were found which can affect the health of the population. Besides this, a high percentage of intestinal parasites that are transmitted through feces were detected indicating fecal contamination and low level of hygiene.